(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Human resource management involves creating personnel policies and procedures that support business objectives and strategic plans. Central to this mission is fostering a culture that reflects core values and empowers employees to be as productive as possible.